Economic Burden of Varicella in Children in Peru from 2011 to 2016 - Castillo, María Esther (2019)
Objective: The purpose of this study was to evaluate the clinical and economic burden associated with varicella in Peru. Methods: This was a multicenter, retrospective chart review study of patients aged 1-14 years with a varicella diagnosis between 2011 and 2016. Healthcare resource utilization (HCRU) associated with varicella, unit costs, and work loss were used to estimate direct and indirect costs, presented in USD ($). The cost and HCRU data was combined with estimates of varicella disease burden to estimate the overall annual costs of management of varicella in Peru. Results: A total of 179 children with varicella (101 outpatients, 78 inpatients) were included. Among outpatients, 5.9% experienced ≥1 complication, compared with 96.2% of inpatients. HCRU estimates included use of over-the-counter (OTC) medications (72.3% vs. 89.7% of outpatient and inpatients, respectively), prescription medications (30.7% vs. 94.9%), tests/procedures (0.0% vs. 80.8%). Among outpatients, direct and indirect costs per case were $36 and $62, respectively; among inpatients, respective costs were $548 and $222. The total annual cost associated with varicella was estimated at $ 13 907 146. Conclusion: Varicella is associated with substantial clinical complications and high HCRU in Peru, supporting the need for implementation of a routine childhood varicella vaccination plan.